Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
* \(P\left(x\right)=4x^3-\frac{3}{2}x^2-x+10\)
\(P\left(-2\right)=4\cdot\left(-2\right)^3-\frac{3}{2}\cdot\left(-2\right)^2-\left(-2\right)+10\)
\(=4\cdot\left(-8\right)-6+2+10\)
\(=-26\)
* H(x) + Q(x) = P(x)
<=> H(x) = P(x) - Q(x)
H(x) = \(4x^3-\frac{3}{2}x^2-x+10-\left(10-\frac{1}{2}x-2x^2+4x^3\right)\)
= \(4x^3-\frac{3}{2}x^2-x+10-10+\frac{1}{2}x+2x^2-4x^3\)
= \(\frac{1}{2}x^2-\frac{1}{2}x\)
* H(x) luôn nguyên với mọi x
Chỗ này bạn xem lại đề
a, Ta có : \(P\left(-2\right)=4\left(-2\right)^3-\frac{3}{2}\left(-2\right)^2-\left(-2\right)+10\)
\(=-32.\left(-6\right)+2+10=192+2+10=204\)
b, \(H\left(x\right)+Q\left(x\right)=P\left(x\right)\)
\(H\left(x\right)=P\left(x\right)-Q\left(x\right)\)
\(H\left(x\right)=4x^3-\frac{3}{2}x^2-x+10-10+\frac{1}{2}x+2x^2-4x^3\)
\(=\frac{1}{2}x^2-\frac{1}{2}x\)